Wild Carnivore Survey of Echinococcus Species in Slovenia - Petra Bandelj; Rok Blagus; Gorazd Vengušt; Diana Žele Vengušt (Animals, 2022)
Wild carnivores are definitive hosts and potential reservoirs for the tapeworm Echinococcus sp. which can cause cystic and alveolar echinococcosis. Both are considered neglected and important food-borne pandemics. This study is the first to molecularly test Slovenian wild carnivores for Echinococcus species that can cause disease in humans. Fecal samples from 210 red foxes (Vulpes vulpes), 42 wolves (Canis lupus), 39 golden jackals (Canis aureus), 18 martens (Marten sp.), 2 Eurasian lynx (Lynx lynx), 2 European badger (Meles meles), and 1 Eurasian otter (Lutra lutra) were examined for Echinococcus granulosus sensu lato (EGsl: E. granulosus sensu stricto, E. canadensis) and E. multilocularis (EM) using real-time PCR. Red foxes (29.1%) and golden jackals (18%) were positive for EM. All animals examined were negative for EGsl. Univariate analysis showed no significant differences in EM prevalence with respect to animal species (red fox vs., golden jackal) (p = 0.22), age (p = 0.12), and sex (p = 0.18). Prevalence of EM was associated with the region (p < 0.001), with regions in central and southern Slovenia having higher EM prevalence and risk of infection. Due to the increase in population and expansion of habitat, the golden jackal may soon become as important definitive host for EM as the red fox.